Chromobodies to Quantify Changes of Endogenous Protein Concentration in Living Cells - Keller, Bettina-Maria (Mol Cell Proteomics, 2018)
Understanding cellular processes requires the determination of dynamic changes in the concentration of genetically nonmodified, endogenous proteins, which, to date, is commonly accomplished by end-point assays in vitro. Molecular probes such as fluorescently labeled nanobodies (chromobodies, CBs) are powerful tools to visualize the dynamic subcellular localization of endogenous proteins in living cells. Here, we employed the dependence of intracellular levels of chromobodies on the amount of their endogenous antigens, a phenomenon, which we termed antigen-mediated CB stabilization (AMCBS), for simultaneous monitoring of time-resolved changes in the concentration and localization of native proteins. To improve the dynamic range of AMCBS we generated turnover-accelerated CBs and demonstrated their application in visualization and quantification of fast reversible changes in antigen concentration upon compound treatment by quantitative live-cell imaging. We expect that this broadly applicable strategy will enable unprecedented insights into the dynamic regulation of proteins, e.g. during cellular signaling, cell differentiation, or upon drug action.